An Inclusive Social Health Insurance for People with Disabilities in Three Southeast Asia Countries: A Systematic Review - Abdallah Kafaa, Kafa; Nurhadi, Nurhadi (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
This article examines how inclusiveness is implemented for People with Disabilities (PWDs) in social health insurance programs in Southeast Asia by focusing on the National Health Insurance (NHI) in Indonesia, the National Health Insurance Program (NHIP) in the Philippines, and Social Health Insurance (SHI) in Vietnam. The concept of inclusive social insurance for PWDs is used as an analytical tool to explore inclusivity criteria, such as target specifications, service benefits, multi-stakeholder involvement, service functions, and the program's impact. Drawing on the qualitative systematic review method, which refers to Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), PRISMA Protocols 2015, and evidence-based guidelines, this article analyzes 25 selected pieces of literature. The results of the study show that: First, there are no special schemes and mechanisms in those programs that target PWDs directly and specifically. Second, those programs have not been able to meet the specific health needs of PWDs. Third, the implementation of those programs has involved three stakeholder actors: the state, the private sector, and NGOs. Fourth, those programs have not shown a significant impact on improving the health quality of PWDs. Finally, it can be concluded that the three programs are not yet truly inclusive in covering PWDs in social health insurance programs.